Effects of Fermented Soybean Meal Substituting Plant Protein and Fish Meal on Growth, Flesh Quality, and Intestinal Microbiota of Largemouth Bass (Micropterus salmoides) - Beibei Guo; Lingling Huang; Xiaoqin Li; Yunfeng Chen; Tianyu Huang; Lizhou Ma; Xiangjun Leng (Aquaculture Nutrition)
This study investigated the effects of replacing soybean meal (SM), corn gluten meal (CGM), and fish meal (FM) with fermented soybean meal (FSM) on growth performance, flesh quality, and intestinal microbiota of largemouth bass. In a diet with 400 g/kg FM inclusion (FSM-0), FSM was used to substitute 120 g/kg SM, 120 g/kg SM + 80 g/kg CGM, and 65 g/kg FM at the inclusion of 100 g/kg (FSM-10-SM), 200 g/kg (FSM-20), and 100 g/kg (FSM-10-FM), respectively. Then, largemouth bass weighing 225.7 ± 2.6 g was fed the four diets for 60 days. The WG of FSM-20 group was increased by 11.8% (P<0.05), while FSM-10-SM and FSM-10-FM groups did not differ significantly from FSM-0 group in growth performance. Compared with the FSM-0 group, the flesh hardness, shear force, total collagen, hot soluble collagen, and total free amino acid contents of FSM-20 group were significantly increased, and FSM-10-SM group also presented higher flesh hardness and shear force. The flesh superoxide dismutase (SOD) and total antioxidant capacity (TAOC) activities in FSM-20 and FSM-10-FM groups and glutathione peroxidase (GSH-Px) activity in FSM-10-FM group were increased (P<0.05), while the lactic acid content in FSM-20 group was decreased, when compared to FSM-0 group (P<0.05). In serum biochemical indexes, the glucose, total protein, cholesterol and malondialdehyde contents in the three FSM groups, and the triglyceride content in FSM-10-SM and FSM-20 groups were significantly lower than those of FSM-0 group (P<0.05). In intestinal histology, the intestinal villus width, muscle thickness in FSM-10-SM group and intestinal villus width in FSM-20 group were significantly higher than those of FSM-0 group. In intestinal microbiota, the three FSM groups showed higher abundance of Firmicutes and lower abundance of Proteobacteria than FSM-0 group. In summary, the replacement of 120 g/kg SM or 65 g/kg FM with 100 g/kg FSM (FSM-10-SM and FSM-10-FM groups) did not exhibit significant effect on growth performance, but partially improved the flesh quality of largemouth bass. The substitution of 120 g/kg SM + 80 g/kg CGM with 200 g/kg FSM (FSM-20 group) significantly improved weight gain and flesh quality of largemouth bass.